Clinical impact of nanophotonic blue-light filtering spectacles based on fullerene C60 and polymethyl methacrylate (PMMA) - Jankov, Mirko R.; Jakšić, Vesna; Koruga, Djuro (Vojnosanitetski pregled, 2021)
Background/Aim. Blue light might be harmful to the retina. The nano-material based on fullerene C60 and polymethyl methacrylate (PMMA) transforms the light into harmonized light and absorbs violet, blue, and ultraviolet (UV) wavelength. The aim of the study was to evaluate the subjective and objective impact of the spectacles on daily activities. Methods. Twenty-five healthy participants were submitted to contrast sensitivity (CS) and visual field (VF) testing and a questionnaire about the influence of spectacles on daily activities: two spectacles with different concentrations of fullerene C60 vs. two commercially available blue-blocking spectacles. Results. There was no statistical difference in CS (p = 0.83), in VF parameters: mean deviation (MD) (p = 0.36), pattern standard deviation (PSD) (p = 0.25), number of relative scotomas (p = 0.31), while the number of absolute scotomas showed a statistically significant decrease (p < 0.05). Spectacles B (with a lower concentration of fullerene – 0.025%) had the best overall comfort mean score (p < 0.00001): four-fifths of participants performed better only during the day, while two-thirds performed better both during the day and night. Spectacles B were also superior in overall satisfaction regarding all combined daily activities (4.04 ± 1.1) (p = 0.0008). Conclusion. Blue-blocking filters with fullerene C60 increase the overall comfort of daily tasks during and after their use. These filters might be an effective mechanism that can protect us from ocular pathologies while providing better comfort in daily activities.